PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BACA AL-QUR’AN DI SD NEGERI 168 REJANG LEBONG - Sundari, Jerri; Botifar, Maria (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2026)
This study aims to describe the role of Islamic Religious Education teachers in increasing students' interest in reading the Qur'an at SD Negeri 168 Rejang Lebong. The problem of low reading interest was found at various grade levels, characterized by the inability to recognize the hijaiyah letters and limited mastery of tajwid. This study used a descriptive qualitative approach through observation, interviews, and documentation. The results showed that Islamic Religious Education teachers implemented learning strategies in the form of an individual approach, habituating reading before the lesson began, using appropriate learning methods, providing religious motivation, and collaboration with parents. These strategies were proven to improve reading skills while building student interest despite still facing obstacles such as lack of home support and limited study time. This study concluded that the role of Islamic Religious Education teachers is crucial in fostering students' love of the Qur'an through a planned, directed, and sustainable strategy.